2005
DOI: 10.1534/genetics.104.038745
|View full text |Cite
|
Sign up to set email alerts
|

Two Hybridization Events Define the Population Structure of Trypanosoma cruzi

Abstract: Genetic variation in Trypanosoma cruzi is likely a key determinant in transmission and pathogenesis of Chagas disease. We have examined nine loci as markers for the extant T. cruzi strains. Four distinct alleles were found for each locus, corresponding to the sequence classes present in the homozygous discrete typing units (DTUs) I, IIa, IIb, and IIc. The alleles in DTUs IIa and IIc showed a spectrum of polymorphism ranging from DTU I-like to DTU IIb-like, in addition to DTU-specific sequence variation. DTUs I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
259
2
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(303 citation statements)
references
References 68 publications
32
259
2
10
Order By: Relevance
“…This result agrees with the hypothesis that DTU IIb and IIc may be the hybrid IId/IIe parentals (Machado and Ayala, 2001 ;Gaunt et al 2003 ;Brisse et al 2003 ;Elias et al 2005 ;Westenberger et al 2005). Recently, using 5S rRNA analysis it was confirmed that the hybrids IId/IIe are heterozygous and have sequences from DTU IIb and IIc (Westenberger et al 2006).…”
Section: Discussionsupporting
confidence: 89%
“…This result agrees with the hypothesis that DTU IIb and IIc may be the hybrid IId/IIe parentals (Machado and Ayala, 2001 ;Gaunt et al 2003 ;Brisse et al 2003 ;Elias et al 2005 ;Westenberger et al 2005). Recently, using 5S rRNA analysis it was confirmed that the hybrids IId/IIe are heterozygous and have sequences from DTU IIb and IIc (Westenberger et al 2006).…”
Section: Discussionsupporting
confidence: 89%
“…To obtain the greatest effectiveness, the new recommendations for the naming of T. cruzi will require a simple and reproducible schema for typing isolates into their respective DTUs. Lewis et al (2009) described such a schema using currently available markers in the form of a triple assay that employed rDNA PCR (Souto et al 1996) and PCR-RFLP of the HSP60 and GPI loci (Westenberger et al 2005). The expert committee is exploring the possibility of a multicentric study to standardise and validate different protocols for genotyping reference and laboratory strains, as well as field isolates.…”
Section: Recommendations Of the Second Satellite Meeting -(I)mentioning
confidence: 99%
“…This was first documented by the existence of hybrid organisms in sylvatic T. cruzi populations and sympatric clinical strains and, later, experimentally (Gaunt et al 2003 and cited references). The prevailing view is that DTU I and DTU IIb are ancient lineages and that DTU IId and DTU IIe strains are the products of a minimum of two hybridisation events (Westenberger et al 2005, Freitas et al 2006, Tomazi et al 2009). The evolution of DTU IIa and DTU IIc strains is insufficiently understood for the moment, although these DTUs may also have a hybrid origin (Sturm et al 2003, Westenberger et al 2005.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No, at least not until we have the wealth of new data that will soon emerge from comparative genomics, more widespread availability of simple methods to distinguish them, and clarification of which species definition should apply. Additionally, it is clear from numerous sequencing studies (Machado and Ayala, 2001 ;Brisse et al 2003 ;Westenberger et al 2005 ;Broutin et al 2006) that TcII does not represent a monophyletic group (TcIIc for example is, at most loci, more genetically similar to TcI than to TcIIb). Should TcIIa and TcIIc be merged ?…”
Section: N O M E N C L a T U R E A N D T A X O N O M I C C O N S I D mentioning
confidence: 99%